A contribution to understanding "čefurke" - Antić, Milica G. (Annales. Series historia et sociologia, 2014)
The paper deals with migratory processes from the area of the former Yugoslavian republics towards Slovenia, focusing primarily on women migratory population. By combining theoretical knowledge with empirical findings the article tries to shed light on the poorly researched immigration processes in Slovenia, despite the fact that immigration rate has exceeded emigration rate already since the 1960s. Its main perspective proceeds from personal narrations which transgress the usual monochromic conclusions and expose the need to study women's migration in a contextualized perspective. The main methodology used rely on the oral history method of collecting life stories; a free, conversational method of gathering information about migratory experiences, which also reveals new perspectives, new research questions.
Keywords: human migration; Jugoslavija; migracije; priseljenke; Slovenia; Slovenija; woman; Yugoslavia; zgodovina migracij; ženske; življenjske zgodbe